Teachers' understanding of the importance of students' mother tongue(s) in Qatar's international English-medium primary schools: findings from Q method research. Issue 1 (1st January 2022) - Alkhateeb, Hadeel; Alshaboul, Yousef
ABSTRACT: Through Q methodology, this study explores teachers' understanding of the importance of their students' mother tongue(s) in ensuring meaningful, effective learning in Qatar's international English-medium primary schools. It considers the extent to which teachers believe that their students' linguistic backgrounds are affirmed and promoted. The results indicate that the teachers provided conflicting narratives, revealing that they embraced their schools' declared multilingual policies yet did not seem to act as agents of implementation. In conclusion, this study argues that teachers' understanding of the matter under investigation is hampered by their poor preparation, ideological bias as native/near-native English language speakers and lack of initial training and continuing professional development in ESL education.